Modeling the processes that control fine sediments transport in the Río de la Plata estuary - Simionato, Claudia Gloria (2018)
Numerical models are excellent tools for conducting process studies and testing hypotheses based on observations. They constitute a "virtual laboratory" in which the forcings can be set "on" or "off", or even the environmental conditions can be modified. The Rio de la Plata (RdP) is one of the most turbid estuaries in the world and the one most important in terms of continental discharge and drainage area. Observations of suspended fine sediments, particularly those remote and in situ collected on recent studies, have driven to the statement of several hypotheses about the processes that would determine the concentration of suspended sediments in the different parts of the estuary. Nevertheless, the relative scarcity of data do not allow to demonstrate the validity of those hypothesis and the role of several physical processes and of the morphology remain unknown. The objective of this work is, therefore, to analyze the role of the different forcing and the environmental conditions in the determination of the distribution of suspended fine sediments in the RdP applying processes oriented numerical simulations.